Quality parameters, pollen and volatile profiles of honey from North and Central Mozambique. (30th March 2019) - Tanleque-Alberto, Fernando; Juan-Borrás, Marisol; Escriche, Isabel
Highlights: Pollen spectrum more than geographical origin distinguishes Mozambiquean honey. Vegetation and apicultural practices influence in the characteristics of these honeys. According to the similar pollen spectrum, eight groups of types of honey were found. High HMF, moisture and smoke compounds are consequence of apicultural practices. Abstract: Honey from different provinces of North and Central Mozambique was characterised considering their physicochemical quality parameters, colour, sugars, total antioxidants, pollen analysis and volatile profile. Flora that surrounds the hives, and the apicultural practices also influence in their characteristics. According to a similar pollen spectrum, eight types of honey were found. In these, the predominant pollens were: I-Astragalus type; II- Acanthus sp; III-Celastraceae; IV-Brassicaceae; V-Anacardiaceae and Astragalus type; VI-Astragalus type and Myrtaceae; VII-Asteraceae family and VIII-unknown. Group I (from Nampula), especially distanced itself from the others mainly due to the special abundance of certain compounds (alcohols, aldehydes, esters, acids and terpenes). The presence of furan compounds largely identified in Sofala and Manica honeys could be due to inadequate beekeeping practices or storage conditions. A discriminant analysis correctly classified 96.7% of the groups, being electrical conductivity and moisture followed by the volatile-compound 3-Methylbutan-1-ol and the free acidity, the variables that most contributed.